Fluorescent GPCR Ligands as New Tools in Pharmacology-Update, Years 2008- Early 2014 - J. Kuder, Kamil; Kiec-Kononowicz, Katarzyna (Current Medicinal Chemistry, 2014)
The robust of fluorescent techniques to study the ligand-receptor interaction followed by rapidly developing fluorescence imaging techniques resulted in a burst of the novel fluorescent ligands development. Taking into consideration not only ligand’s high affinity to the receptor, but also their fluorescent properties to visualize the interaction even in the single cell level, gives the researchers a strong impulse to investigate that field of GPCR ligands. Moreover, paying attention to the “non pharmacological” advantages of these ligands, as well as the techniques to be used, fluorescent ligands become commonly used pharmacological tools to study GPCRs. Herein we report on the results described in the literature since late 2007 in the field of the fluorescent GPCR small, non-peptide ligands according the receptor affinity, fluorophores that has been used to tag the molecules and their fluorescent properties as well as their application in GPCR research.
Keywords: Dimerization